Видовий склад плодових рослин України та перспективи їхнього використання - Mezhenskyj, V.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The data of species composition of aboriginal and introduced fruit plants in Ukraine are presented. There are about 1000 species from 124 genera and 49 families growth on the territory of Ukraine including 206–258 local species of 49 genera and 24 families, and more than 760 introduced species of 109 genera and 42 families. 110 species and interspecies hybrids of 50 genera and 22 families are economically important.